2003
DOI: 10.1086/367638
|View full text |Cite
|
Sign up to set email alerts
|

The Baldwin Effect and Black Hole Accretion: A Spectral Principal Component Analysis of a Complete Quasar Sample

Abstract: We have performed a spectral principal component analysis (SPCA) for an essentially complete sample of 22 low redshift QSOs with spectral data from Lyα to Hα. SPCA yields a set of independent principal component spectra, each of which represents a set of relationships among QSO continuum and line properties. We find three significant principal components, which account for ∼78% of the total intrinsic variance. The first component, carrying ∼41% of the intrinsic variance, represents Baldwin relationships -anti-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
5
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 53 publications
10
102
5
1
Order By: Relevance
“…Figure 5 plots the first two SPCs, which together account for 48.8% of the variance. SPC1 has emission lines narrower than the mean spectrum, and is roughly consistent with both the SPC1s of Francis et al (1992) and Shang et al (2003), and the Intermediate Line Region (ILR) spectrum of Brotherton et al (1994) (see also Pâris et al 2011). SPC2 is dominated by continuum variation suggestive of dust reddening, along with some associated emissionline variation.…”
Section: Spectral Principal Component Analysis (Spca)supporting
confidence: 77%
“…Figure 5 plots the first two SPCs, which together account for 48.8% of the variance. SPC1 has emission lines narrower than the mean spectrum, and is roughly consistent with both the SPC1s of Francis et al (1992) and Shang et al (2003), and the Intermediate Line Region (ILR) spectrum of Brotherton et al (1994) (see also Pâris et al 2011). SPC2 is dominated by continuum variation suggestive of dust reddening, along with some associated emissionline variation.…”
Section: Spectral Principal Component Analysis (Spca)supporting
confidence: 77%
“…We also did not see any Baldwin effect for this set of lines, although it was found by Shang et al (2003) for Oi line.…”
Section: Resultscontrasting
confidence: 43%
“…Continuum and emission lines are believed to originate from the hot accretion disc and circumnuclear fast moving clumps, correspondingly. The proximity of these regions is considered to be the most promising explanation of the Baldwin (1977) effect: the inverse correlation of EW of some emission lines with the monochromatic luminosities at UV region, e. g., for Lyα (1215Å), Siii (1260Å), Oi (1304Å), Siiv+Oiv] (1400Å) lines (see e. g. Dietrich et al 2002, Green, Forster & Kuraszkiewicz 2001, and Shang et al 2003. But the physical explanation of the difference in α λ and relation of quasar luminosity and lines' EW to α λ are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…This set of correlations was found to be the primary eigenvector of the emission line correlation matrix of PG quasars studied by Boroson & Green (1992). This eigenvector 1 was later found to correlate with UV properties such as C iv shift/asymmetry (Marziani et al 1996), Si iii]/C iii] ratio, and C iv and N v strength (Wills et al 1999;Shang et al 2003). Since eigenvector 1 was found to correlate significantly with X-ray properties (Laor et al 1997;Brandt & Boller 1998), which are determined in the vicinity of the central black hole, it was suggested that differences in emission line properties revealed by eigenvector 1 are caused by differing central engine parameters (e.g., L/L Edd , accretion rate, orientation, and/ or black hole spin).…”
Section: Introductionmentioning
confidence: 87%
“…In reality, the scatter of the Baldwin effect is too large to give meaningful results, and studies have concentrated on understanding and reducing this scatter (Shang et al 2003;Dietrich et al 2002). Conflicting results have also emerged, where radio-loud samples and samples with a wide range of luminosities show a stronger effect (e.g., Baldwin et al 1978;Wampler et al 1984;Kinney, Rivolo, & Koratkar 1990;Wang, Lu, & Zhou 1998), while radio-quiet samples and samples with a small luminosity range show weaker or no effect (e.g., Steidel & Sargent 1991;Wilkes et al 1999).…”
mentioning
confidence: 99%